State of a Lowland Tropical Forest in South-West Nigeria - Wakawa, L.D.; Ogana, F.N.; Adeniy, T.E. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2018)
Forests play a significant role in human existence and survival. Timely and reliable information on the status of a forest is essential for assessing the extent of regeneration and degradation. However, when such information is lacking effective forest management practices becomes impossible. Therefore, this study assessed the tree species diversity, richness and structure of Oluwa forest reserve with the view of ascertaining it present state which is crucial for management and conservation purposes. To achieved these, a systematic line transect was used in the laying of eight (8) temporary sample plots (TSPs) of size 50m x 50m. Trees with Dbh≥10cm in the selected plots were enumerated, identified and measured. The results indicate that 535 individual trees were enumerated cutting across 26 families and 58 species. The reserve has the Margalef's index of species richness, Shannon-Weiner diversity Index (H') and Pielou's Species Evenness Index (EH) of 9.07, 3.43 and 0.84 respectively. The forest has a mean Dbh (cm), mean height (m), total basal area/ha (m2) and total volume/ha (m3) of 24.7, 16.9, 36.63 and 602.09 respectively. Majority of trees were found in the smaller diameter and height classes; giving rise to reverse J-shaped structure. The structure of Oluwa forest reserve has been altered significantly while the species diversity and richness seems to indicate a sign of improvement compared to previous studies. With proper management, the remaining fragmented forests could regenerate and replenish to save some of the original species composition of the reserve.
Keywords: Lowland tropical forest, tree species diversity, forest structure, forest conservation